Great world religions Hinduism - Muesse, Mark William 1957- (Great courses, 2003)
Provides an overview of Hinduism and discusses why Hinduism is perhaps the most diverse religion of all. Covers topics such as arranged marriages and the caste system, the Indus Valley Civilization, the sacred writings in the Vedas, the Bhagavad-gita, and the Upanishads, ritual purity rites, the Aryan language of Sanskrit, and Hinduism's rejection of the notion that there is but one path to the divine. Introduces Hinduism's wealth of gods, terms, and practices, such as Krishna, karma, guru, and yoga.